ROLE OF ALTERATION OF CK5\6 PROFILE IN DYSPLASTIC PROGRESSION OF ORAL MUCOSA IN TOBACCO USERS - Batool, Sarwat; Fahim, Amin; Qureshi, Aneela; Jabeen, Humaira; Ali, Syed Naqeeb; Khoso, Mohammad Yousuf (Journal of Ayub Medical College Abbottabad, 2020)
Background: To determine staining expression of CK5\6 in healthy oral mucosa and various grades of oral dysplasia and to find out the possible association of CK5\6 expression in the dysplastic transformation of clinically normal oral mucosa to various grades of oral dysplasia. Methods: This cross-sectional descriptive study was done at Al-Tibri Medical College and Hospital and Dow University of Health Sciences, Karachi from March 2018 to November 2018. It included 120 diagnosed paraffin-embedded tissue samples of normal oral mucosa and various grades of oral epithelial dysplastic lesions. The patient's data were reviewed for age, gender, and tobacco habits. For immunohistochemistry CK5\6 staining was performed on all the samples. Immunohistochemical evaluation was done by observing the staining expression of CK5\6 on various oral dysplastic samples on the basis of staining intensity. The compiled data were statistically analyzed by using Chi-square. p-values of <0.05 were considered to be significant. Results: All of the 60/60 (100%) oral dysplastic cases were moderate to strongly positive for CK5\6. A gradual increase in staining intensity for CK5\6 was observed with increasing grades of dysplasia. We found a highly significant association of CK5\6 immunopositivity in the transformation of normal mucosa to various grades of oral dysplastic lesions. Conclusion: CK5\6 can be used as a reliable adjuvant marker for the early dysplastic transformation of oral mucosa in tobacco users before it progresses to oral squamous cell carcinoma (OSCC). Keywords: Oral dysplastic lesions; CK5\6; Oral squamous cell carcinoma